Artemisinin drugs: novel antimalarial agents. - Price, R (2000)
Artemisinin and its derivatives, artesunate and artemether, represent a new class of antimicrobial drug with potent activity against Plasmodium falciparum. Although they show excellent efficacy in both severe and uncomplicated malaria, dosage regimens still need to be optimised and pharmacokinetic profiles defined. In the treatment of uncomplicated malaria, the artemisinin drugs should be used in combination with a long acting antimalarial to protect both drugs against the emergence of resistance. In the treatment of severe malaria, parenteral artemether is at least as effective as quinine and is simpler to use. The use of rectal preparations of artesunate and artemisinin at the rural health level will facilitate early initiation of the treatment of falciparum malaria and this may reduce the proportion of patients progressing to severe disease. All of the artemisinin drugs have comparable efficacy; the choice of derivative should be based upon availability, cost and quality of the preparation. Artemisinin, artesunate and artemether are well-tolerated in both adults and children, with no evidence to date of serious clinical toxicity.